Pea (Pisum sativum l.) Plant Shapes Its Rhizosphere Microbiome for Nutrient Uptake and Stress Amelioration in Acidic Soils of the North-East Region of India - Chaudhari, Diptaraj; Rangappa, Krishnappa; Das, Anup; Layek, Jayanta; Basavaraj, Savita; Kandpal, Basant Kumar; Shouche, Yogesh; Rahi, Praveen (Frontiers in Microbiology, 2020)
Rhizosphere microbiome significantly influences plant growth and productivity. Legume crops like pea have often been used as a rotation crop along with rice cultivation in long-term conservation agriculture experiments in the acidic soils of the North-East Region of India. It is essential to understand how the pea plant influences the soil communities and shapes its rhizosphere microbiome. It is also expected that the long-term application of nutrients and tillage practices may also have a lasting effect on the rhizosphere and soil communities. In this study, we estimated the bacterial communities by 16S rRNA gene amplicon sequencing of pea rhizosphere and bulk soils from a long-term experiment with multiple nutrient management practices and different tillage history. We also used Tax4Fun to predict the functions of bacterial communities. Quantitative PCR was used to estimate the abundance of total bacterial and members of Firmicutes in the rhizosphere and bulk soils. The results showed that bacterial diversity was significantly higher in the rhizosphere in comparison to bulk soils. A higher abundance of Proteobacteria was recorded in the rhizosphere, whereas the bulk soils have higher proportions of Firmicutes. At the genus level proportion of Rhizobium, Pseudomonas, Pantoea, Nitrobacter, Enterobacter, and Sphingomonas was significantly higher in the rhizosphere. At the same time, Massilia, Paenibacillus and Planomicrobium were more abundant in the bulk soils. Higher abundance of genes reported for plant growth-promotion, and several other genes including iron complex outer membrane receptor, cobalt-zinc-cadmium resistance, sigma-70 factor and ribonuclease E was predicted in the rhizosphere samples in comparison to bulk soils, indicating that the pea plants shapes its rhizosphere microbiome, plausibly to meet its requirements for nutrient uptake and stress amelioration.